First Record of Northern Pike Esox lucius (Actinopterygii: Esociformes: Esocidae) in the Kuti Lake Area (Mala Neretva) - Jurinović Jure; Pilić Vesna; Bonačić Kruno; Prečanica Mario; Barić Oliver (Croatian Journal of Fisheries)
This paper describes the first record of northern pike Esox lucius (Linnaeus, 1758) in Kuti Lake (Mala Neretva, Croatia). A specimen of this species was caught in Kuti Lake in November 2024. The presence of pike has been recorded in tributaries and reservoirs of the Neretva River in Bosnia and Herzegovina, but its presence in the Neretva River system in Croatia presents an expansion of the distribution of the species. Although local fishermen and sources from grey literature in recent years indicate that this species is already present in the area where this specimen was caught, further research is needed to determine the mode of introduction and whether a stable population is present in the area.